Building Communities of Trust Creative Work for Social Change - E. Feldman, Ann (Routledge Focus on Media and Cultural Studies, 2022)
Drawing upon a combination of ethnographic research and media and communication theory, Building Communities of Trust: Creative Work for Social Change offers pathways to building trust in a range of situations and communities. Ann Feldman presents rich examples from her own life and social-impact journey with nonprofit, Artistic Circles, along with supplemental case studies from interviews with 20 to 30-year-olds, to address how to create vibrant, trust-based societies and to determine what works and what doesn't while advancing towards creating social impact. These case studies and shared experiences from real life media projects across 30 years, reveal behind-the-scenes stories of challenges, conflicts, and resolutions in global impact efforts ranging from women's empowerment to water access. The book explains how the success - or failure - of social-impact initiatives depends on power struggles, funding, interpersonal misunderstandings, identity crises, fears, and stereotypes. The book's goal is to help aspiring changemakers develop strategies for sustainable social-change projects. It serves as a guide for undergraduates, graduate students, and high-school upperclassmen in environmental studies, business, sociology, gender and sexuality, cross-cultural studies, music, religion, and communications and media. For more on Artistic Circles and Ann E Feldman's work, please visit https://www.buildingcommunitiesoftrust.org/ The Open Access version of this book has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license: https://www.taylorfrancis.com/books/oa-mono/10.4324/9781003296423/building-communities-trust-ann-feldman